Essai sur l’étude de la coopération bilatérale entre le Canada et l’Afrique francophone 1961-1981 - Houndjahoué, Michel (Études internationales, 1982)
We have divided the evolution of bilateral cooperation between Canada and the French-speaking countries of Africa into three major phases. During the first phase, which lasted from 1961 to 1968, Canadian aid was slight and discontinuous. The second phase, from 1969 to 1975, was characterized by a remarkable increase of the CIDA 's activities. That period was specially influenced, on the one had, by the rudeau and Chevrier missions and, on the other hand, by the reconsideration of Canada's foreign policy during the 1970's. The third phase, from 1975 to 1981, was arked, among other things, by what one could call industrial cooperation, that is cooperation between « project-countries » and « program-countries ». We have tried to analyse the main characteristics of each of those three phases, while striving to « link » them to the socio-economic and political context of Canada and the French-speaking countries of Africa.